2011
DOI: 10.1177/0269215510397394
|View full text |Cite
|
Sign up to set email alerts
|

Clinical measurement of walking balance in people post stroke: a systematic review

Abstract: The multiple-task outcome measures reviewed reflected walking balance activities often undertaken during community mobility. Single-task measures may be useful as screening measures, identifying walking balance deficits associated with basic/lower levels of walking balance. Construct validity and clinical interpretability of each measure in ambulatory people post stroke requires further research to identify the level of community mobility represented by each measure of walking balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 38 publications
0
64
0
5
Order By: Relevance
“…Paired t-test revealed that there was no systematic difference between the test -retest measures with p>0.05. Relative reliability measure of ICC value was 0.92, which revealed it was > 0.8 and indicates it has excellent reliability 21 . Absolute reliability measures of SEM showed it has 2.56 mm and for MDC it was 7.09 mm, when assessing subjects for DM using real time ultrasound.…”
Section: Resultsmentioning
confidence: 91%
“…Paired t-test revealed that there was no systematic difference between the test -retest measures with p>0.05. Relative reliability measure of ICC value was 0.92, which revealed it was > 0.8 and indicates it has excellent reliability 21 . Absolute reliability measures of SEM showed it has 2.56 mm and for MDC it was 7.09 mm, when assessing subjects for DM using real time ultrasound.…”
Section: Resultsmentioning
confidence: 91%
“…The test-retest reliability level was determined by looking at the intraclass correlation coefficient (ICC); poor (ICC <0.4), moderate (ICC 0.4 to 0.8) and excellent (>0.8) [19,20]. Table 1 Paired t-test analysis found no significant difference in the mean value of knee angles at all the three planes of motion between the two measurement sessions (all p > 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…To assess intra-and interrater reliability of DWSs A and B during EO and EC, intraclass correlation coefficient (ICC) [1,3] with 95 percent confidence interval was used [22]. ICC value >0.8 indicated excellent reliability, 0.4 to 0.8 indicated adequate reliability, and <0.4 indicated poor reliability [23]. Bland-Altman plot was employed to measure agreement of LLA values of DWS with MatScan.…”
Section: Discussionmentioning
confidence: 99%